2012
DOI: 10.1371/journal.pone.0029632
|View full text |Cite
|
Sign up to set email alerts
|

Post-GWAS Functional Characterization of Susceptibility Variants for Chronic Lymphocytic Leukemia

Abstract: Recent genome-wide association studies (GWAS) have identified several gene variants associated with sporadic chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL). Many of these CLL/SLL susceptibility loci are located in non-coding or intergenic regions, posing a significant challenge to determine their potential functional relevance. Here, we review the literature of all CLL/SLL GWAS and validation studies, and apply eQTL analysis to identify putatively functional SNPs that affect gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 53 publications
3
26
0
Order By: Relevance
“…Multiple SNPs are in perfect linkage disequilibrium (LD) ( r 2 ≥ 0.90; D ′ ≥ 0.98) with the top CD-associated intronic SNPs rs7423615 and rs6716753 (Fig. 4A) (16, 17), including those associated with CLL (rs13397985) (18) and MS (rs10201872) (19), and hence may act coordinately (hereafter collectively referred to as SNP +/+ ). All of these SP140 SNPs are intronic, except for a single SNP in exon 7 (rs28445040) that was recently suggested to be the causal SNP (45).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple SNPs are in perfect linkage disequilibrium (LD) ( r 2 ≥ 0.90; D ′ ≥ 0.98) with the top CD-associated intronic SNPs rs7423615 and rs6716753 (Fig. 4A) (16, 17), including those associated with CLL (rs13397985) (18) and MS (rs10201872) (19), and hence may act coordinately (hereafter collectively referred to as SNP +/+ ). All of these SP140 SNPs are intronic, except for a single SNP in exon 7 (rs28445040) that was recently suggested to be the causal SNP (45).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we report on SP140, a previously uncharacterized immune-restricted epigenetic reader that has previously reported SNPs that associate with CD (16, 17), CLL (18), and MS (19). We show that individuals bearing CD-associated SP140 SNPs, most of which are intronic and in perfect LD with SP140 SNPs associated with CLL and MS, have alterations in SP140 mRNA splicing that ultimately result in loss of SP140 protein, consistent with the findings from a recent publication (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single nucleotide polymorphisms (SNPs) in several genetic loci like 8q24, 22q13 and 17q12 were reported to be linked to PCa susceptibility, early onset of the disease and tumor agressiveness (Al Olama, et al, 2014; Berndt, et al, 2015; Chang, et al, 2009; Cheng, et al, 2009; Eeles, et al, 2009; Eeles, et al, 2013; Gudmundsson, et al, 2009; Helfand, et al, 2015; Levin, et al, 2008; Salinas, et al, 2008; Schumacher, et al, 2011; Takata, et al, 2010; Thomas, et al, 2008; Witte, 2007). Although little is known about the functional aspect of risk SNPs, some studies showed cancer SNPs predominately present in multiple putative regulatory elements (2011; Sille, et al, 2012). SNPs in the promoter of the KLK3 gene, encoding the commonly used PCa marker protein prostate specific antigen (PSA), were reported to increase serum PSA and PSA promoter activity (Cramer, et al, 2003), while a C→T substitution of SNP rs10993994:C>T in the 5′ region of the prostate cancer suppressor gene MSMB was shown to affect gene expression level (Chang, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sp140 localization to PML-NBs, which are subnuclear structures involved in the regulation of gene transcription, cellular growth, apoptosis and maintenance of chromatin architecture [9], along with the presence of several chromatin related modules in its primary structure, suggest a role in chromatin-mediated regulation of gene expression. Indeed coactivator activity was inferred for Sp140 by virtue of its Gal4 DNA-binding domain fusion activity in transfected COS cells [10,11]; it has therefore been hypothesized that Sp140 might regulate the expression of genes involved in CLL development [5]. In line with its putative role in transcriptional regulation, Sp140 has strong sequence homology with autoimmune regulator (AIRE), a transcriptional activator governing the ectopic expression of peripheral tissue-specific antigens in the thymus [12].…”
Section: Introductionmentioning
confidence: 99%